Ocorrência e flutuação populacional de Chrysopidae (Neuroptera) em áreas de plantio de Pinus taeda (L.) (Pinaceae) no sul do Paraná - Cardoso, Josiane Teresinha; Lázzari, Sonia Maria Noemberg; Freitas, Sérgio de [UNESP]; Iede, Edson Tadeu (Sociedade Brasileira de Entomologia, 2003)
The lacewings are very voracious predators of aphids. The objective of this research was to evaluate the occurrence of adult chrysopids in areas of Pinus reforestation where the giant conifer aphid Cinara spp. (Hemiptera: Aphididae) is causing severe damages. A total of 47 specimens were collected during one year and identified as: Chrysoperla externa (Hagen, 1861), Leucochrysa (Nodita) intermedia (Scheneir, 1851) and Leucochrysa (Nodita) vieirana (Navás, 1913). The captures in the area where the plants were one year old represented about 75% of the adults probably due to the high Cinara infestation on the trees in this area. The chrysopids were recorded mostly during the summer, possibly influenced by temperature.
Occurrence and population fluctuation of Chrysopidae (Neuroptera) on Pinus taeda (L.) (Pinaceae) in Southern Paraná
Keywords: Giant conifer aphids; insect survey; Lacewings; traps